On the study of archaeometallurgical slag by X-Ray fluorescence analysis method - Sharonov Iosif A.; Alibekov Akbar S.; Reutova Marina A.; Khaidarov Umidjon E.; Minjee OH. (Поволжская археология)
The results of X-ray fluorescence analysis of an ancient slag sample from an iron-smelting furnace found in the foothills of the Nurata Ridge in Uzbekistan are presented. The main purpose of the work is to consider the influence of pressing of powdered slag samples on the results of X-ray fluorescence analysis. It is demonstrated that it is possible to make X-ray fluorescence analysis of powder of archaeometallurgical slag without pressing it. Comparison of the results of measurements of analytical slag samples made on different energy dispersive spectrometers (manual spectrometer Vanta Element S and desktop spectrometer Shimadzu EDX-7000) was made. It is noted that it is necessary to control the normalisation of the registered results given by the measurement protocols of spectrometers.